Development of a Novel Laparoscopic Palpation System Using a Wearable Motion-Sensing Armband - Caballas, Kerwin G (Archīum Ateneo, 2021)
This study proposes the development of a novel palpation system for use in the laparoscopic surgery setting, which relies on a wearable motion-sensing armband worn on the palpating arm. The system is tested by prodding the laparoscopic tool on a simulated human tissue with an anomaly underneath and measuring the effects of the forces experienced by the palpating arm by recording the accelerometer data embedded in the armband. Results show that the proposed system could detect the anomalies embedded in the gelatin phantom based on the change of the amplitude of the accelerometer data. A decrease in the average peak-to-peak amplitude of accelerometer signal by as much as 32.29% was observed for the single point prodding experiment, while a decrease of up to 22.93% was observed for the raster scan experiment. The results from this feasibility experiment confirmed the potential role of the accelerometer signal in the motion-sensing armband in being able to assist laparoscopic palpation.